Computational Characterizations of the Interactions Between the Pontacyl Violet 6R and Exoribonuclease as a Potential Drug Target Against SARS-CoV-2 - Munaweera, Rangika; Hu, Ying S. (Frontiers in Chemistry, 2021)
We report a molecular-docking and virtual-screening-based identification and characterization of interactions of lead molecules with exoribonuclease (ExoN) enzyme in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). From previously identified DEDDh/DEEDh subfamily nuclease inhibitors, our results revealed strong binding of pontacyl violet 6R (PV6R) at the catalytic active site of ExoN. The binding was found to be stabilized via two hydrogen bonds and hydrophobic interactions. Molecular dynamics simulations further confirmed the stability of PV6R at the active site showing a shift in ligand to reach a more stabilized binding. Using PV6R as the lead molecule, we employed virtual screening to identify potential molecular candidates that form strong interactions at the ExoN active site. Our study paves ways for evaluating the ExoN as a novel drug target for antiviral treatment against SARS-CoV-2.